Psychological Effects of Orthodontic Treatment in Adults: A Mixed-Methods Study - Shresthaa Singh; Khumanthem Savana; Brajendu; Parul Priya; Abhay K. Jain; Abhishek Kumar (Journal of Pharmacy and Bioallied Sciences)
Background: Orthodontic treatment is often pursued to improve dental aesthetics and function, but its psychological effects on adult patients are not well-documented. Materials and Methods: This mixed-methods study involved 150 adult participants undergoing orthodontic treatment. Quantitative data were collected using the Oral Health Impact Profile (OHIP-14) questionnaire and the State-Trait Anxiety Inventory (STAI) before treatment, mid-treatment, and posttreatment. Qualitative data were gathered through semistructured interviews with 30 participants, selected via purposive sampling, to explore their personal experiences and perceptions of the treatment process. Quantitative data were analyzed using Analysis of Variance (ANOVA) to assess changes over time, while thematic analysis was conducted on qualitative data to identify common themes. Results: Quantitative analysis revealed significant improvements in OHIP-14 scores (P < 0.001), indicating enhanced oral health-related quality of life posttreatment. Anxiety levels, as measured by STAI, decreased significantly from baseline to posttreatment (P < 0.01). Qualitative interviews highlighted themes of increased self-esteem, improved social interactions, and initial discomfort during the adaptation phase of treatment. Participants reported a heightened awareness of oral health and a positive shift in self-image. Conclusion: Orthodontic treatment in adults leads to significant psychological benefits, including reduced anxiety and improved quality of life.